Tunable plasmonic properties of elongated bimetallic alloys nanoparticles towards deep UV-NIR absorbance and sensing. (January 2020) - Bhatia, Pradeep; Verma, S.S.; Sinha, M.M.
Highlights: The present research is to highlight the studies of bimetallic alloys nanoparticles of magneto-plasmonic nanostructures. The influence of size, shapes, compositions and surrounding medium for Co-Ag and Co-Au alloy nanoparticles results in significant change in optical properties. The spectra are found between 211 and 964 nm wavelengths ranges and can be tuned in the deep UV-NIR region of the electromagnetic (EM) spectrum. Tunability in sizes and shapes opens new potential use with desired applications in biomedical fields. Abstract: Combining magnetic nanoparticles with noble metallic nanoparticles to construct multifunctional alloy nanostructures has become a powerful tool for imaging sensing, medicine, biology, and cancer treatment and photothermal therapy. This work reports a study regarding the plasmonic properties of Co-Ag and Co-Au bimetallic alloys nanostructures on the electromagnetic spectrum. In this paper, the optical properties of magnetic and plasmonic nanoparticles (NPs) with different shapes, sizes, compositions, and surrounding medium are investigated by using the discrete dipole approximation (DDA) technique. The absorption and scattering localized surface plasmon resonance (LSPR) peak positions are found between 211–964 nm wavelengths ranges and can be tuned in the deep UV-NIR region of the EM spectrum in accordance with the desired application. Further, we calculate the refractive index sensitivity (S) and figure of merit (FOM) of LSPR based nanosensors. Although, LSPR based sensors undergo low FOM as compared to conventional surface plasmon resonance (SPR) sensors due to high losses from the radiative damping of localized surface plasmons (LSPs) waves. However, LSPR based sensors have potential applications in gas and bio-sensors technology viz. medical and environmental monitoring applications. In this work, the main feature of LSPR peak is dependent on nanoparticle shapes, sizes, compositions, and ambient medium and have ordered as prolate < sphere < cube < rectangular shape NPs. These results suggest that the nanostructures of Co-Ag and Co-Au alloys associated with LSPR tunability and sensitivity can be used in biomedical and sensing environment technology such as detection of chemical and catalytic events.